2007
DOI: 10.1111/j.1467-2494.2007.00356.x
|View full text |Cite
|
Sign up to set email alerts
|

6‐O glucose linoleate supports in vitro human hair growth and lipid synthesis

Abstract: The hair follicle is a very active organ with a complex structure, which produces a hair fibre at a rate of 0.3 mm a day. Accordingly, the hair follicle is highly demanding in energy source, as the hair bulb matrix cells are endowed with one of the highest rates of proliferation in the human body. Moreover, recent data have shown the involvement of lipids in hair follicle function. As in vitro-grown hair follicle keeps producing a hair fibre that closely resembles the natural hair fibre, we decided to use this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…In addition, the demand for glucose of hair follicles from different regions is inconsistent. Generally, the growth of hair follicles on the head has a higher energy requirement, which is related to the metabolism of glucose and glucose derivatives [ 46 , 47 ]. Moreover, the glucose sensitivity of stem cells activation and differentiation are inconsistent [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the demand for glucose of hair follicles from different regions is inconsistent. Generally, the growth of hair follicles on the head has a higher energy requirement, which is related to the metabolism of glucose and glucose derivatives [ 46 , 47 ]. Moreover, the glucose sensitivity of stem cells activation and differentiation are inconsistent [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, we believe, that when regarding treatment outcomes observed in both women and men, AC5 used in monotherapy and under the study conditions confirmed that combining several ingredients, known for their clinical benefit, notably reduces hair loss. [15][16][17][18] Despite these limitations, AC5 improves hair loss and hair quality in subjects with mild AGA with an excellent tolerability, a pleasant texture, and a high satisfaction rate.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14] Arginine was shown to improve microvascular function in the skin, piroctone olamine to increase hair shaft thickness, SP94 to fortify hair fibers, and VVMW to reduce skin inflammation. [15][16][17][18] Moreover, yet unpublished data have provided evidence that piroctone olamine, as VVMW, decreases inflammation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This model allowed the factors that govern hair growth, hair structure and its 3D shape to being better characterized. [117][118][119][120][121]…”
Section: The Facial Appearance: the "Raison D'être" Of Cosmetic Researchmentioning
confidence: 99%